Racial/ethnic and geographic differences in access to a usual source of care that follows the patient-centered medical home model: Analyses from the Medical Expenditure Panel Survey data - Zo Ramamonjiarivelo; Delawnia Comer-HaGans; Shamly Austin; Karriem Watson; Alicia Matthews (The Beryl Institute, 2018)
This study examined racial and geographic differences in access to a usual source of care (USC) and it further explored these differences among individuals who had a USC that followed the patient-centered medical home (PCMH) model. Using cross-sectional data from the Household Component of the Medical Expenditure Panel Survey (2008-2013), our sample consisted of non-institutionalized US civilians ages 18-85 (n= 146,233; weighted n = 229,487,016). Our analysis included weighted descriptive statistics and weighted logistic regressions. Although 76% of the respondents had a USC, only 11% of them had a USC that followed the PCMH model. Among respondents who had a USC that followed the PCMH model, 80% were White, 13% Black, 5% Asian, and 12% were of Hispanic ethnicity. Across U.S. regions, 88% percent of those who had a USC that followed the PCMH model resided in metropolitan statistical areas (MSAs), 22% resided in the West, 26% in the Northeast, 25% in the Midwest, and 27% in the South. Results from logistic regression analyses indicated that race and ethnicity were not significant predictors of having a USC that followed the PCMH model. Northeastern U.S. residents (OR: 1.30; 95% CI:1.06-1.61) were more likely to have a USC that followed the PCMH model compared with southern residents. In conclusion, only a small percentage of respondents in our sample had a USC with the PCMH model. Further, race and ethnicity were not predictors of having a USC with the PCMH model.